From empiricism to expressivism : Brandom reads Sellars - Brandom, Robert (Harvard University Press, 2015)
Wilfrid Sellars ranks as one of the leading critics of empiricism--a philosophical approach to knowledge that seeks to ground it in human sense experience. Robert Brandom clarifies what Sellars had in mind when he talked about moving analytic philosophy from its Humean to its Kantian phase and why such a move might be of crucial importance today.